CARDS FOR COLLECTION OF BIOMATERIAL SAMPLES: AREAS OF APPLICATION - Atavliyeva , S.; Mukhamedyarov , D.; Anuarbekova , A.; Tarlykov , P. (Eurasian Journal of Applied Biotechnology, 2022)
Cost-efficient methods for the collection and storage of biological samples are currently in great demand in the life sciences field. The storage of material on a filter paper carrier has been recently introduced as an option. The carrier is a chemically-treated sample collection matrix that lyses cells and preserves DNA spotted onto the paper. A similar paper-based collection of DNA samples is currently used in many areas of research due to its simplicity, safety, and affordable price. Nowadays, a variety of biological samples are suitable for collection with this carrier, including not only blood and buccal epithelial cells but also bacterial, plant, and insect biomaterial. This review will cover the latest application areas of the paper-based biomaterial collection in areas such as healthcare, microbiology, and agriculture.